The effect of respiratory muscle training on swimming performance: a systematic review and meta-analysis - Liu, S.; Gou, P.; Lin, M. (Frontiers in Physiology, 2025)
Introduction: Respiratory muscle training, which targets the inspiratory and/or expiratory muscles to enhance respiratory efficiency, is recognized as a method for improving athletic performance; however, its effectiveness in enhancing swimming performance remains controversial. This study aimed to evaluate the effects of respiratory muscle training on swimming performance.